Rancang Bangun Alat Pendeteksi Sampah Organik dan Anorganik Menggunakan Sensor Proximity dan NodeMCU ESP8266 - Memen Akbar; Sri Devi Anjasmara; Kartina Diah K Wardhani (Politeknik Caltex Riau, 2021)
Waste products are increasing every day in line with the increasing number of products and people's consumption patterns. Many people do not separate organic and inorganic waste during disposal. One of the reasons is that people cannot distinguish between organic and inorganic waste. Based on these problems, an Internet of Things-based tool was designed that uses NodeMCU ESP8266 as its microcontroller. To distinguish organic and inorganic waste, three sensors are used at once, namely proximity infrared, capacitive and inductive sensors. The data read by this tool then turns on the LED according to the type of trash can. In this study, a trash can was also designed that uses an ultrasonic sensor to detect the height of the garbage. This altitude information is then sent to a website-based monitoring application using a Wi-Fi network and the MQTT protocol. This application is used by cleaners to monitor which trash bins have to be transported. From the test results, the three proximity sensors used succeeded in distinguishing organic and inorganic waste. The recommended distance for the sensor to work optimally is 3 mm. The data obtained by the sorting tool has also been successfully sent to the waste height monitoring application. Officers get notifications on the website, which trash bins must be transported.